Blue Emitting BaAl2O4:Ce3+ Nanophosphors with High Color Purity and Brightness for White LEDs. (December 2019) - Chatterjee, Rituparna; Saha, Subhajit; Panigrahi, Karamjyoti; Ghorai, Uttam Kumar; Das, Gopes Chandra; Chattopadhyay, Kalyan Kumar
Abstract: In this work, strongly blue emitting Ce 3+ -activated BaAl2 O4 nanophosphors were successfully synthesized by a sol–gel technique. The crystal structure, morphology, and microstructure of the nanophosphors have been studied by X-ray powder diffraction, field emission scanning electron microscopy, and high-resolution transmission electron microscopy. The photoluminescence spectra show the impact of concentration variation of Ce 3+ on the photoluminescence emission of the phosphor. These nanophosphors display intense blue emission peaking at 422 nm generated by the Ce 3+ 5 d → 4 f transition under 350 nm excitation. Our results reveal that this nanophosphor has the capability to take part in the emergent domain of solid-state lighting and field-emission display devices.